Pelatihan Pembuatan Tepung Talas untuk Meningkatkan Kemandirian Ekonomi Bagi Kelompok Tani di Desa Sungai Malaya Kalimantan Barat - Syamsuri, Syamsuri; Alang, Hasria; Mashudi, Mashudi; Safira, Pretty; Wulandari, Rizty (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to enhance the knowledge and skills of the 'Usaha Maju Bersama' farmer group in Sungai Malaya Village, West Kalimantan, in producing taro flour as a healthy food commodity based on the creative economy. The methods employed include community education, science and technology diffusion, training, and the Asset-Based Community Development (ABCD) approach. Data analysis was conducted by comparing pretest and posttest results given before and after the training. The activity resulted in a significant increase in partners' knowledge and skills in making taro flour, from 56% to 87%. The implication of this activity is that partners now possess flouring machines, enabling them to produce taro flour.